Mice lacking Nf1 in osteochondroprogenitor cells display skeletal dysplasia similar to patients with neurofibromatosis type I - Wang, Weixi (Oxford University Press, 2011)
Mutations in NF1 cause neurofibromatosis type I (NF1), a disorder characterized, among other clinical manifestations, by generalized and focal bony lesions. Dystrophic scoliosis and tibial pseudoarthrosis are the most severe skeletal manifestations for which treatment is not satisfactory, emphasizing the dearth of knowledge related to the biology of NF1 in bone cells. Using reporter mice, we report here that the mouse Col2α1-Cre promoter (collagen, type II, alpha 1) is active not only in chondrocytes but also in adult bone marrow osteoprogenitors giving rise to osteoblasts. Based on this finding, we crossed the Col2α1-Cre transgenic and Nf1(flox/flox) mice to determine whether loss of Nf1 in axial and appendicular osteochondroprogenitors recapitulates the skeletal abnormalities of NF1 patients. By microtomographic and X-rays studies, we show that Nf1(Col2)(−/−) mice display progressive scoliosis and kyphosis, tibial bowing and abnormalities in skull and anterior chest wall formation. These defects were accompanied by a low bone mass phenotype, high bone cortical porosity, osteoidosis, increased osteoclastogenesis and decreased osteoblast number, as quantified by histomorphometry and 3D-microtomography. Loss of Nf1 in osteochondroprogenitors also caused severe short stature and intervertebral disc defects. Blockade of the RAS/ERK activation characteristic of Nf1(−/−) osteoprogenitors by lovastatin during embryonic development could attenuate the increased cortical porosity observed in mutant pups. These data and the skeletal similarities between this mouse model and NF1 patients thus suggest that activation of the RAS/ERK pathway by Nf1 loss-of-function in osteochondroprogenitors is responsible for the vertebral and tibia lesions in NF1 patients, and that this molecular signature may represent a good therapeutic target.